Concise encyclopaedia of bioinformatics and computational biology - Hancock, John M.;Zvelebil, Marketa (Hoboken, New Jersey : John Wiley & Son, Inc., 2014)
oncise Encyclopaedia of Bioinformatics and Computational Biology, 2nd Edition is a fully revised and updated version of this acclaimed resource. The book provides definitions and often explanations of over 1000 words, phrases and concepts relating to this fast-moving and exciting field, offering a convenient, one-stop summary of the core knowledge in the area. This second edition is an invaluable resource for students, researchers and academics.
List of contributors -- Preface -- Entries A to Z -- Author index.
Includes bibliographical references and index.
Keywords: BIOINFORMATICS -- DICTIONARIES